Perancangan Mesin CNC Acrylic Cutting 3 Axis Dengan Menggunakan Laser Tube CO2 - Elvando andha elvaris manalu; Asmed Asmed; Mulyadi Mulyadi; Yuliarman Yuliarman; Ruzita Sumiati (Politeknik Negeri Padang, 2023)
Almost all activities are carried out with the help of technology. It is as if technology has become a basic need for human life today. Of all the areas that have made progress, machinery is the one that has had the greatest effect. Lots of machines have emerged with new innovations with very diverse functions, one of which is the Computer Numerical Control (CNC) machine. A CNC machine is a machine used in the manufacturing industry to quickly produce large quantities of components for the engineering sector. As the name of the CNC itself, every work from CNC uses a computer system that has been well formed to produce goods that are in accordance with what is desired. Departing from some of the problems above, the author concluded to make a similar technology at a much cheaper price with a more practical work system, therefore the author made a 3 Axis Acrylic Cutting CNC Machine Using a CO2 Laser Tube